HALAL CRITICAL POINT OF MICROBIAL BIOPROCESS BASED-DAIRY PRODUCTS - Kurniati, Kurniati; Hafsan, Hafsan (Universitas Islam Negeri Alauddin Makassar, 2022)
The dairy products that use certain enzymes and microbial cells to produce other product variants such as yoghurt and cheese are products that which must be observed for its halalness. Uses microbial and additional ingredients and auxiliary materials that are not necessarily halal.The bacteria commonly used in the processing of dairy products such as yoghurt and cheese are several species of the lactic acid bacteria group which are developed as a starter in the fermentation process. Generally, lactic acid bacteria are grown first on growth media before being used as a starter. The halal critical point is the growth media, which contain proteins to own chances of animals (such as beef extract) which can be derived from pigs. Non-halal sources of carbon and nitrogen in growth media, such as blood, can also cause bacterial cells and microbial products to have a haram status. The same thing in the process of finalizing processed dairy products with the addition of flavours, amino acids, preservatives, or gelatine. The addition of food additives has become a critical point in any case because it can be a microbial product that needs to be ascertained halal. This review reveals that the critical point in making yoghurt is in milk as its raw material, the step of adding starter and adding additives. While the critical point in cheese making is in milk as its raw material and at the coagulation stage.